Beta-glucan-depleted, glycopeptide-rich extracts from Brewer's and Baker's yeast (Saccharomyces cerevisiae) lower interferon-gamma production by stimulated human blood cells in vitro. (15th April 2016) - Williams, Roderick; Dias, Daniel A.; Jayasinghe, Nirupama; Roessner, Ute; Bennett, Louise E.
Highlights: Yeasts are known for their immune-modulatory activity related to cell-wall β-glucans. Glycopeptide-enriched, β-glucan-depleted products were prepared from dietary yeasts. Fractionation resolved pro- and anti-inflammatory activity using a human blood cell assay. Abstract: Regulation of the human immune system requires controlled pro- and anti-inflammatory responses for host defence against infection and disease states. Yeasts ( Saccharomyces cerevisiae ), as used in brewing and baking, are mostly known for ability to stimulate the human immune-system predominantly reflecting the pro-inflammatory cell wall β-glucans. However, in this study, using food-compatible processing methods, glycopeptide-enriched and β-glucan-depleted products were each prepared from Brewer's and Baker's yeasts, which suppressed production of interferon-γ (IFN-γ) in human whole blood cell assay, signifying that anti-inflammatory factors are also present in yeast. Anti-inflammatory bioactivities of products prepared from Brewer's and Baker's yeast were compared with the commercial yeast product, Epicor®. While unfractionated Epicor was inactive, the C18 resin-binding fractions of Brewer's and Baker's yeast products and Epicor dose-dependently lowered IFN-γ, demonstrating that Epicor also contained both pro-inflammatory (β-glucans) and anti-inflammatory components. Anti-inflammatory activity was attributed to C18 resin-binding species glyco-peptides in Epicor and experimental yeast products. This study demonstrated that pro- and anti-inflammatory factors could be resolved and enriched in yeasts by suitable processing, with potential to improve specific activities.